Magnetic resonance imaging for characterization of hepatocellular carcinoma metabolism - Wang, Lixia; Yang, Ju Dong; Yoo, Charles C.; Lai, Keane K. Y.; Braun, Jonathan; McGovern, Dermot P. B.; Xie, Yibin; Pandol, Stephen J.; Lu, Shelly C.; Li, Debiao (Frontiers in Physiology, 2022)
With a better understanding of the pathophysiological and metabolic changes in hepatocellular carcinoma (HCC), multiparametric and novel functional magnetic resonance (MR) and positron emission tomography (PET) techniques have received wide interest and are increasingly being applied in preclinical and clinical research. These techniques not only allow for non-invasive detection of structural, functional, and metabolic changes in malignant tumor cells but also characterize the tumor microenvironment (TME) and the interactions of malignant tumor cells with the TME, which has hypoxia and low pH, resulting from the Warburg effect and accumulation of metabolites produced by tumor cells and other cellular components. The heterogeneity and complexity of the TME require a combination of images with various parameters and modalities to characterize tumors and guide therapy. This review focuses on the value of multiparametric magnetic resonance imaging and PET/MR in evaluating the structural and functional changes of HCC and in detecting metabolites formed owing to HCC and the TME.